Field and Laboratory Hydraulic Characterization of Landslide‐Prone Soils in the Oregon Coast Range and Implications for Hydrologic Simulation - Ebel, B.A. (2020)
This investigation focused on hydraulic property estimation for soil in a landslide‐prone area where the relative importance of hysteresis is unclear. Laboratory measurements of soil‐water retention from field soils in the Oregon Coast Range during wetting and drying show that pronounced hydraulic hysteresis is present. In contrast, a 4‐yr field data record of pore‐water pressure and soil‐water content from multiple soil pits at the same landslide‐prone area shows relatively minor hydraulic hysteresis compared with the laboratory estimates. Simulated subsurface hydrologic response parameterized using estimates from field data more closely matched hydrologic observations relative to model parameterization based on laboratory analysis of repacked soil samples. Our results suggest that (i) unsaturated hydraulic parameter estimates based on in situ field data, as opposed to laboratory measurements alone, may lead to more accurate simulation of the hydrologic response to rainfall, (ii) in situ data of soil‐water retention may need to include values at both high suctions and near saturation to improve estimates of soil hydraulic parameters for slope failure applications, and (iii) laboratory measurements of soil‐water retention made under dynamic conditions may overestimate hydraulic hysteresis.